Role of Probiotic, Prebiotic and Synbiotic on Growth Performance and Biometric Development of Jaffarabadi Buffalo Calves - A Pata, Bharat; R Gadariya, Mahesh; V Gamit, Viral; H Savsani, Harish; D Odedra, Mulraj; P Sabapara, Ghanshyam (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was aimed to investigate the effects of probiotic, prebiotic and synbiotic supplementation on growth performance and biometric parameters in Jaffarabadi buffalo calves. A total of 24 neonatal calves were divided into four equal groups: Control (C), Probiotic (T1), Prebiotic (T2) and Synbiotic (T3), each consisting of six calves. The calves were fed a restricted suckling diet, supplemented with basal feed and each group received specific additives: T1 (probiotic), T2 (prebiotic) and T3 (synbiotic). The experiment was conducted for 175 days, from 8 to 182 days of age. Results showed that calves in the T1, T2 and T3 groups exhibited significantly higher growth rates compared to the control group (p<0.01). The overall body weight gain in the early and late post-natal phases was higher by 10.17%, 8.44% and 13.50% in the probiotic, prebiotic and synbiotic groups, respectively. Synbiotic supplementation resulted in the highest average daily gain (402.71 g/d). Significant improvements were also observed in body length, height at withers and chest girth, with the T3 group demonstrating the highest increase in chest girth. The study concludes that probiotic, prebiotic and especially synbiotic supplementation positively influence growth performance and biometric development in Jaffarabadi buffalo calves, suggesting their potential utility for improving calf health and productivity under tropical conditions.